2012
DOI: 10.1080/00288233.2011.643904
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur and lime response of four adventive annual clovers grown in a New Zealand high country soil under glasshouse conditions

Abstract: Adventive annual clovers play a critical role in nitrogen (N) cycling and feed quality in extensive summer-dry hill country, where traditionally sown white and subterranean clovers often fail to persist. However, very little is known about the edaphic (e.g. soil fertility) requirements of these species. The growth response and nutrient uptake of four adventive annual clovers to applied sulphur (S) or lime, grown in a typical low-fertility South Island high country soil, were investigated under glasshouse condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Previous studies with this soil excluded a role for excessive Ca uptake [Ca is a potent antitranspirant ( De Silva et al , 1985 )] in limiting leaf gas exchange and biomass accumulation of legume crops ( Rothwell and Dodd, 2014 ). However, tissue or xylem sap P concentrations of limed plants were consistently decreased ( Table 2 ), as in previous observations where liming decreased yield ( Haynes, 1982 ; Maxwell et al , 2012 ). While further investigations of soil P dynamics seem advisable, adding CaCO 3 could precipitate large quantities of CaHPO 4 , thereby making P unavailable to the plant ( Delgado and Torrent, 2000 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies with this soil excluded a role for excessive Ca uptake [Ca is a potent antitranspirant ( De Silva et al , 1985 )] in limiting leaf gas exchange and biomass accumulation of legume crops ( Rothwell and Dodd, 2014 ). However, tissue or xylem sap P concentrations of limed plants were consistently decreased ( Table 2 ), as in previous observations where liming decreased yield ( Haynes, 1982 ; Maxwell et al , 2012 ). While further investigations of soil P dynamics seem advisable, adding CaCO 3 could precipitate large quantities of CaHPO 4 , thereby making P unavailable to the plant ( Delgado and Torrent, 2000 ).…”
Section: Discussionsupporting
confidence: 86%
“…However, liming responses are not always positive, and yield reductions can occur even at recommended application rates. This has been attributed to changes in tissue Ca:Mg ratios ( Carran, 1991 ), Mg fixation within the soil ( Sumner et al , 1978 ), or reduced P availability ( Haynes, 1982 ; Maxwell et al , 2012 ). More recent work tested the hypothesis that unregulated Ca uptake by the plant increased root xylem sap calcium ion (Ca 2+ ) concentration or delivery rate, causing a stomatal limitation of photosynthesis that may limit growth of limed legumes.…”
Section: Introductionmentioning
confidence: 99%
“…The application of lime is used to increase soil pH in agricultural systems. However this practice is often uneconomic on extensive farms due to high aerial application costs (Maxwell et al 2014). Legumes which are able to persist and thrive in low pH soils, or with low inputs of lime and P, would be well suited to this environment and could be of major benefit to dryland farming systems.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has also been conducted in Australia investigating subterranean clover (T. subterraneum) responses to added P (Paynter 1993;Bolland & Paynter 1994;Bolland 1995;Cayley & Hannah 1995;Cayley et al 1998). The literature addressing P responses of T. subterraneum and naturalized adventive annual legumes under New Zealand conditions is limited (Beale et al 1993;Dodd & Orr 1995;Maxwell et al 2010Maxwell et al , 2012. In a pot trial using two P rates, Caradus (1980) reported a P response by striated, haresfoot and suckling clovers.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a larger suite of field and climatecontrolled experiments examining the role of adventive annual clovers in extensively grazed high and hill country environments (Maxwell et al 2010(Maxwell et al , 2012.…”
Section: Introductionmentioning
confidence: 99%